A Wearable Triboelectric Nanogenerator Based on Polyester‐Paper Cloth for Mechanical Energy Harvesting and Running Motion Sensing - Xu Deng (ChemistryOpen)
Abstract Paper‐based triboelectric nanogenerators (P‐TENGs) have recently garnered significant attention in wearable electronics. However, traditional P‐TENGs are constrained by the inherent strength limitations of paper. Hence, we reported a novel polyester‐paper cloth‐based triboelectric nanogenerator (PP‐TENG) designed for mechanical energy harvesting and running motion monitoring. Compared to paper, polyester‐paper cloth has higher durability and tear resistance. The PP‐TENG capitalizes on the unique fluffy internal structure of polyester‐paper cloth, imparting high sensitivity to pressure variations. Experimental results demonstrate that the PP‐TENG achieves an open‐circuit voltage (Voc) of 466.64 V, a short‐circuit current (Isc) of 48.73 μA, and a transfer charge (Qsc) of 90 nC. Its maximum output power reaches 930.26 μW when connected to a 40 MΩ load. These impressive metrics underscore the potential of PP‐TENG in energy harvesting applications, particularly for wearable electronic devices. The device's integration into the soles of athletic socks showcases its practical utility, providing real‐time monitoring of runners’ gait and step count. This integration not only enhances the functionality of sportswear but also offers valuable data for performance analysis and injury prevention, marking a significant advancement in wearable technology and intelligent textiles. This research provide a promising path for self‐powered wearable sensors and flexible electronics applications.